Akibat Hukum dari Wanprestasi dalam Transaksi Jual Beli Secara Instagram - Ryan Prastya Mariata Putra; Ida Ayu Putu Widiasti; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2020)
The influence of globalization that occurs today has made information and communication technology became something very important for society because it presents a world without boundaries, distance, space, and time. This has made changes to the lifestyles of the people as well as changed the social, economic, cultural, security, and law enforcement. This research was conducted with the aim of describing the rights and obligations of the parties in an Instagram trade agreement and the legal consequences of negligence on an Instagram trade agreement. This research was conducted using normative legal research methods. The results of this study showed that the rights and obligations of the parties to the engagement on Instagram are regulated in the PK Law. Consumers and business actors have their respective rights and obligations. In addition, the legal consequences for a debtor/party who has the obligation to perform in the engagement but has committed negligence, namely: he must pay compensation suffered by the creditor/party who has the right to receive achievement (vide Article 1243 of the Civil Code); he must accept the decision of the engagement accompanied by payment of compensation (vide Article 1267 of the Civil Code); he must accept the transfer of risk from the moment of failure (vide Article 1237 paragraph (2) of the Civil Code); and he must pay court fees if litigated in court (vide Article 181 paragraph (1) HIR).